Democracy on Social Media: The Analysis of the New Criminal Code Ratification Polemic on Twitter - Anbarini, Ratih; Abdullah, Aceng; Sjafirah, Nuryah Asri (Jurnal Kajian Jurnalisme, 2023)
The new Criminal Code (Kitab Undang-undang Hukum Pidana/KUHP) passage on December 6, 2022, sparked a significant conversation on Twitter, with pro and con responses making it a trending topic. Among these responses, certain influential actors disseminated messages that had the potential to shape public opinion, even if the information was not always accurate. This research utilizes social network theory to map the conversations surrounding netizens’ reactions to the new Criminal Code ratification on social media platforms. The study employs descriptive social network analysis methods to analyze three key variables: network structure, groups, and actors. Data was collected using NodeXL Pro between December 6 to December 10, 2022. The findings revealed that although the network consisted of 25,245 actors and 59,396 relationships, the level of interconnectivity among actors was relatively loose, indicating weaker and mostly one-way relationships. Furthermore, influential actors came from diverse backgrounds and profiles. This research confirms the ability of social media platforms to connect individuals without physical face-to-face interactions. At the group level, discussions regarding the new Criminal Code were divided into various topics, highlighting different perspectives and opinions. The presence of diverse actors reflects the inclusive nature of the network, exemplifying the concept of digital opinion movements and the emergence of digital public spaces. Although the public protests did not change the government’s decision, the conversations among netizens regarding the new Criminal Code raised public awareness of national issues, a crucial aspect of digital democracy.